Contested value and an ethics of resources: Water, mining and indigenous people in the Atacama Desert, Chile - Babidge, Sally (The Australian journal of anthropology, 2016)
The question of value is fundamental to contexts of resource scarcity given that contest over use and distribution of scarce resources centres on judgments about rights, interests and access. In mining processes, the use and extraction of water in great volumes commodifies and threatens supplies of what others understand to be a substance essential to all forms of life. In the Atacama, while industrial extraction and commodification by the mining industry are the basis for indigenous people's contestations over water resources, an analysis of everyday water practice and performance (as ‘ordinary ethics’) demonstrates that an indigenous ethics of resources includes commodity values under certain conditions. This paper examines a field of competing actors engaging in extraction and use of scarce waters in order to make an argument for the importance of considering the complexities and dynamics of ethical practice and water value.